The relationships between symptoms, disability, perceived health and quality of life in amyotrophic lateral sclerosis/motor neuron disease. Issue 5 (3rd July 2019) - Young, Carolyn Anne; Ealing, John; McDermott, Christopher; Williams, Tim; Al-Chalabi, Ammar; Majeed, Tahir; Burke, Georgina; Pinto, Ashwin; Dick, David; Talbot, Kevin; Harrower, Timothy; Walsh, Jannette; et al.
Abstract: Objectives : Using the Wilson and Cleary model linking clinical variables to quality of life, we explored the associations between physical and psychological factors, disability, perceived health and quality of life in ALS/MND. Methods : The ongoing UK study of Trajectories of Outcomes in Neurological Conditions (TONiC) recruited participants with ALS/MND to complete a questionnaire pack including demographic factors and several patient reported outcome measures (PROMs); a clinician provided data on disease onset type and duration since diagnosis. All PROMs were transformed from ordinal raw scores to interval-scaled latent estimates via the Rasch measurement model. Results : Data from 636 patients were analyzed; mean age 65.1 years (SD 10.7), 61.3% male. Median duration since diagnosis was 11.2 months (IQR 4.6–29.9; range 0.4–295.9 months); 67.3% had limb and 27.3% bulbar onset disease. Symptoms such as breathlessness and fatigue, along with most domains of activity limitations, were shown to vary by onset type. A series of models illustrated the importance of physical functioning and anxiety upon quality of life, with breathlessness and fatigue having indirect effects. The models were invariant for gender and onset type. Conclusions : This large study highlights the importance of functional status and anxiety as key variables influencing quality of life in ALS/MND. The nature and diversity of factors, both physical and psychological, which have been shown to influence the quality of life of people with ALS/MND provide strong evidence in support of the widespread implementation of multidisciplinary care.